Higher Music Teacher Education Programs in Mexico from the Professors’ Perspective. A Descriptive Study - Capistrán Gracia, Raúl Wenceslao (2024)
Introduction: Despite the significant promotion and undeniable growth of music education in Mexico, three major issues have hindered its full consolidation and appropriate development: 1) There are few higher music education programs; 2) Enrollment in these programs is extremely low; 3) There is a deficit of well-trained music educators. Unfortunately, few studies in Mexico have addressed these issues, with most focusing on curriculum design. Objective. To address these concerns, this study conducted a quantitative, descriptive analysis to determine the profile of tertiary music education faculty and explore their perceptions regarding the functioning of their academic programs, their students’ profiles, and the teaching-learning conditions. Methodology. Data was collected through an ad hoc survey created by the researcher and validated through the expert-judgment validation process. The survey was sent to the 14 music education programs listed in the ANUIES Yearbook 2022-2023. Data was statistically analyzed by using the software SPSS, 2.0. Results. The findings highlighted the strengths and weaknesses perceived by professors and provided insights that may explain the current situation. Conclusions. While there are notable strengths, significant weaknesses need to be addressed, including the hiring of more well-prepared full-time professors, the implementation of effective recruitment mechanisms, adequate psycho-pedagogical support, and appropriate funding programs.